Isolation, Characterization, Antibiogram and Molecular Detection of Antibiotic Resistance Genes from Bacteria Isolated from Otitis Externa in Dogs - Doshi, Dhruvi M.; Bhanderi, Bharat B.; Mathakiya, Rafiyuddin A.; Nimavat, Vipul R.; Jhala, Mayurdwaj K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Otitis externa is one of the most common diseases of the canines, defined as an acute or chronic inflammation of the external ear canal. In the present study, 124 samples were collected, out of which 94 samples were from 75 dogs suffering from otitis externa and 30 from 15 healthy dogs from the regions of Anand and Vadodara districts of Gujarat. Total 129 bacteria comprised of Staphylococcus spp. (58.40%), Pseudomonas spp. (10.62%), Proteus spp. (10.62%), Streptococcus spp. (7.08%), Corynebacterium spp. (6.19%), E. coli (4.42%), Klebsiella spp. (1.77%) and Enterobacter spp. (0.88%) were isolated from otitic and healthy ears of dogs based upon colonial, microscopic, and biochemical characteristics. The bacterial isolates showed least resistance towards tobramycin (1.51%) followed by enrofloxacin (5.52%), ofloxacin (11.98%), amikacin (15.20), gentamicin (17.07), and amoxycillin clavulanic acid (17.53%), while they showed the highest resistance towards ampicillin (63.90%). The multidrug resistance was detected in 29.46% (34/129) of the total bacterial isolates. Betalactam resistance genes were detected in E. coli, Klebsiella spp., Enterobacter spp. and Pseudomonas spp.; quinolone resistance genes were detected in E. coli, and aminoglycoside resistance genes were detected in E. coli, Proteus spp. and Staphylococcus spp.